Two new species of Coelostoma Brullé, 1835 from South Xizang, China (Coleoptera: Hydrophilidae: Sphaeridiinae) - Jia, Feng-Long; Mai, Zu-Qi (Zootaxa, 2026)
Two new species of the water scavenger beetle subgenus Lachnocoelostoma Mouchamps, 1958, belonging to the genus Coelostoma Brullé, 1835 are described from southern Xizang Autonomous Region of China. Among the new species, Coelostoma (Lachnocoelostoma) change sp. nov. from Mêdog County is notable for its small body size (3.4–3.6 mm in length) and capitate-shaped median lobe of aedeagus. Coelostoma (Lachnocoelostoma) yi sp. nov. from Zhangmu County was co-occurring with Coelostoma (Lachnocoelostoma) gentilii Jia, Aston & Fikáček, 2014, but elytra without serial punctures laterally, male genitalia with median lobe rather slim. Seven species of the genus are known from Xizang up to now. Species diagnoses, detailed descriptions and illustrations of the new species are provided.